2013
DOI: 10.1007/s10597-013-9614-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Lifestyle Interventions to Reduce Cardiovascular Risk in Patients with Severe Mental Disorders: Meta-Analysis of Intervention Studies

Abstract: Patients with severe mental illness have higher prevalences of cardiovascular risk factors (CRF). The objective is to determine whether interventions to modify lifestyles in these patients reduce anthropometric and analytical parameters related to CRF in comparison to routine clinical practice. Systematic review of controlled clinical trials with lifestyle intervention in Medline, Cochrane Library, Embase, PsycINFO and CINALH. Change in body mass index, waist circumference, cholesterol, triglycerides and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 35 publications
4
36
1
4
Order By: Relevance
“…Our finding of significant weight reduction among the shorter duration (≤ 6-months) lifestyle interventions is consistent with prior systematic reviews and meta-analyses [19,20]. Importantly, we were able to expand on these prior reviews by including several recently published reports of large-scale trials of longer duration lifestyle interventions.…”
Section: Discussionsupporting
confidence: 87%
“…Our finding of significant weight reduction among the shorter duration (≤ 6-months) lifestyle interventions is consistent with prior systematic reviews and meta-analyses [19,20]. Importantly, we were able to expand on these prior reviews by including several recently published reports of large-scale trials of longer duration lifestyle interventions.…”
Section: Discussionsupporting
confidence: 87%
“…This prevented us from evaluating how exercise can work in synergy with other health behaviours, such as diet. Although we found no effect on BMI, other reviews have found that exercise does stimulate weight loss in schizophrenia when used alongside dietary advice (National Institute for Health and Care Excellence, 2014), while interventions that focus solely on diet or physical activity alone are unsuccessful for reducing body weight (Bonfioli et al 2012;Fernández-San-Martín et al 2014).…”
Section: Limitations and Future Researchcontrasting
confidence: 76%
“…It is well-established that modest improvements in glycated haemoglobin (HbA 1c ) and blood glucose levels can avoid onset of diabetes and have a significant impact on preventing diabetic complications in the general population [11]. A few reviews have investigated the effect of pharmacological [6, 12] and behavioural [7, 8, 13] interventions on these glycaemic measurements in people with SMI. An older review investigated both pharmacological and behavioural interventions [14].…”
Section: Introductionmentioning
confidence: 99%